Conscious history : Polish Jewish historians before the Holocaust - Aleksiun, Natalia, 1971- (Littman library of Jewish civilization (Series), 2021)
Historical scholarship was one of the lasting legacies of interwar Polish Jewry. This study shows how Polish Jewish historians worked to create a community aware of its past, its cultural heritage, and its achievements while also working to protect its rights as a minority.